Colloidal stability study of Fe3O4-based nanofluids in water and ethylene glycol - dos Santos, Caio C. [UNESP]; Viali, W. R. [UNESP]; Viali, E. S.N.; Marques, R. F.C. [UNESP]; Jafelicci Junior, M. [UNESP] (Springer Nature, 2020)
In this work, we report the synthesis of a new nanofluid (NF) based on magnetic nanoparticles (MNPS) synthesized by the coprecipitation method with high colloidal stability. The MNPS were functionalized with citric acid (Cac), and then, polyethylene glycol, 1000 (PEG1000), was bonded by polycondensation reactions with acid groups on the nanoparticles surface to increase the colloidal stability of the nanofluid. The MNPS were dispersed in an aqueous medium to obtain nanofluid-based magnetic nanoparticles in water (NF-MNPS-W) and in ethylene glycol to obtain nanofluid-based magnetic nanoparticles in ethylene glycol (NF-MNPS-E). The MNPS were characterized by X-ray diffraction and selected area electron diffraction, which confirmed the formation of the crystalline phase of Fe3O4. Transmission electron microscopy was used to confirm the size and morphology of the MNPS. The MNPS had an average diameter of 11.33 ± 3.68 nm. Infrared spectrum of the MNPS allowed the functionalization of the MNPS by Cac and then by PEG1000 to be proved. The colloidal stability of NF-MNPS-W (pH 8) and NF-MNPS-E was evaluated by measurement of Zeta potential (ζ) and dynamic light scattering (DLS) − 25 mV and 112 nm ± 1 nm, respectively. The DLS in the temperature function allowed the stability of the NF to be proved in working conditions.
Keywords: Complex fluids; Coprecipitation; Magnetic nanoparticles; Magnetite; Oxide nanoparticles; Two-step nanofluid